2009
DOI: 10.1037/a0015386
|View full text |Cite
|
Sign up to set email alerts
|

Normes d’imagerie et de fréquence subjective pour 1 760 mots monosyllabiques de la langue française.

Abstract: This study aimed at providing subjective frequency and imageability norms for a sample of 1,760 monosyllabic French words and thereby, increasing the pool of normative data available for research in cognitive science and language processing. The results indicate that the reliability of the estimates is high, with coefficients ranging between .93 and .99 for the frequency and imageability ratings. External validity was investigated by calculating correlations with ratings drawn from all similar studies and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
1
9
1
Order By: Relevance
“…In line with previous work (e.g., Desrochers & Thompson, 2009; Gonthier, Desrochers, Thompson, & Landry, 2009), several reliability estimates were calculated to examine the internal consistency of the collected psycholinguistic ratings. Table 3 lists the average participant-sample correlation as well as Cronbach’s alpha.…”
Section: Resultsmentioning
confidence: 99%
“…In line with previous work (e.g., Desrochers & Thompson, 2009; Gonthier, Desrochers, Thompson, & Landry, 2009), several reliability estimates were calculated to examine the internal consistency of the collected psycholinguistic ratings. Table 3 lists the average participant-sample correlation as well as Cronbach’s alpha.…”
Section: Resultsmentioning
confidence: 99%
“…Desrochers and Thompson (2009) analysed subjective frequency and imageability ratings for 3,600 French nouns and, like our study in Croatian, they found a low but significant positive correlation (r=0.26; p<0.001). In a study of 1,760 monosyllabic French words, Gonthier et al (2009) showed a stronger positive correlation between imageability and subjective frequency (r=0.64; p<0.001). Using linear regression, Gonthier et al (2009) showed that subjective frequency was a significant predictor of imageability only for less frequent words.…”
Section: Relationship Between Imageability and Frequencymentioning
confidence: 99%
“…In a study of 1,760 monosyllabic French words, Gonthier et al (2009) showed a stronger positive correlation between imageability and subjective frequency (r=0.64; p<0.001). Using linear regression, Gonthier et al (2009) showed that subjective frequency was a significant predictor of imageability only for less frequent words.…”
Section: Relationship Between Imageability and Frequencymentioning
confidence: 99%
“…There is reason to question the reliability or validity of objective frequency estimates for some words, and the validity of subjective frequency estimates has also been challenged. Balota et al (2001), for instance, reported results that suggested that subjective estimation of word frequency is codetermined by word characteristics other than the frequency with which words are encountered, such as meaningfulness and the familiarity of orthographic or phonological patterns (see also Baayen, Feldman, & Schreuder, 2006;Gonthier et al, 2009;. One way of identifying items with dubious validity may then be to obtain both objective and subjective frequency estimates for as large a number of words as possible and to cross-validate them against each other.…”
Section: Estimating Lexical Frequencymentioning
confidence: 99%
“…Of all the lexical charac-1995; Zeno, Ivenz, Millard, & Duvvuri, 1995;for Dutch, see, e.g., Baayen et al, 1995;for French, see, e.g., Lété, Sprenger-Charolles, & Colé, 2004;New, Pallier, Brysbaert, & Ferrand, 2004;for German, see, e.g., Baayen et al, 1995; for Greek, see, e.g., Ktori, van Heuven, & Pitchford, 2008; for Portuguese, see, e.g., Marques, Fonseca, Morais, & Pinto, 2007;for Spanish, see, e.g., Alameda & Cuetos, 1995;Sebastián-Gallés, Martí, Cuetos, & Carreiras, 2000). In comparison, the range of alphabetic languages for which subjective frequencies are available is limited (for English, see, e.g., Balota, Pilotti, & Cortese, 2001;Carroll, 1971;Shapiro, 1969;Tryk, 1968;for French, see, e.g., Bonin et al, 2003;Desrochers & Bergeron, 2000;Ferrand et al, 2008;Flieller & Tournois, 1994;Forget, 2005;Gonthier, Desrochers, Thompson, & Landry, 2009), as is the pool of words for which subjective frequency estimates are available in these languages. This imbalance may be attributed, in part, to the cost of collecting such ratings.…”
Section: Word Frequency As a Determinant Of Lexical Processingmentioning
confidence: 99%